2016
DOI: 10.1007/s10877-016-9828-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wearing an N95 filtering facepiece respirator on superomedial orbital infrared indirect brain temperature measurements

Abstract: Purpose To determine any effect of wearing a filtering facepiece respirator on brain temperature. Methods Subjects (n=18) wore a filtering facepiece respirator (FFR) for 1h at rest while undergoing infrared thermography measurements of the superomedial periobital region of the eye, a non-invasive indirect method of brain temperature measurements we termed the superomedial orbital infrared indirect brain temperature (SOIIBT) measurement. Temperature of the facial skin covered by the FFR, infrared temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…According to Figure 4 , Sample E shows the highest thermal conductivity at 0.0006955 and 0.0012134 W/cm °C, regardless of whether a filter is used. Several cases have suggested that there is a positive correlation between air permeability and thermal conductivity, because the entrapped still air appears to provide significantly more insulation than the fibers and thus retains the heat in the in-mask atmosphere [ 29 , 32 , 33 ]. However, the test results of the masks appear to indicate little correlation between thermal conductivity and air resistance (R 2 = 0.05), which could be because air permeability is not influenced by the material used for masks, whereas this is not true for thermal conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…According to Figure 4 , Sample E shows the highest thermal conductivity at 0.0006955 and 0.0012134 W/cm °C, regardless of whether a filter is used. Several cases have suggested that there is a positive correlation between air permeability and thermal conductivity, because the entrapped still air appears to provide significantly more insulation than the fibers and thus retains the heat in the in-mask atmosphere [ 29 , 32 , 33 ]. However, the test results of the masks appear to indicate little correlation between thermal conductivity and air resistance (R 2 = 0.05), which could be because air permeability is not influenced by the material used for masks, whereas this is not true for thermal conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…a Statistically significant at P<0.05, computed by paired Student's t-test. caused by effects on core temperature but may be associated with warming of facial skin covered by the respirator and warming of inspired air [28,29]. Poor communication and speech intelligibility have been shown to be concerns when wearing a respirator, given the potential for miscommunication that leads to critical treatment mistakes [12].…”
Section: P¼0417mentioning
confidence: 99%
“…Research studies addressing physiological responses to N95 filtering facepiece respirators (N95 FFR), at sedentary and low-moderate work rates in temperate ambient environments over 1–2 hr, have reported no significant effects on core (intestinal, rectal) temperatures [1,6] or on indirect measurements of brain temperature. [7] The temperature of the facial skin under an N95 FFR rises above baseline values and regularly reaches the level at which facial heat sensory receptors are activated and transmit afferent impulses to the brain, [7,8] thereby suggesting that this is the site of origination of respiratory protective equipment-associated heat perceptions. Thus, actions that serve to decrease the temperature of facial skin covered by this equipment may decrease thermal sensations and, secondarily, improve comfort and tolerance.…”
Section: Introductionmentioning
confidence: 99%